Armut in Malerei und Plastik. - Neuer Landtag, Düsseldorf (Düsseldorf : ISG Sozialeforschung und Gesellschaftspolitik, 1989)
Beumer, Veronika Isabella ; Brede, Eberhard ; Brunner, Werner ; Czech, Rainer Joshua ; Eckert, Harald ; Fekete, Gabriella ; Genz, Joe ; Meise, Christine ; Peters, Hildegund
Exhibition of international artists living in the federal republic of Germany. sponsored by the ISG Sozialforschung und Gesellschaftspolitik, Cologne, FRG, Animation and Dissemination servrice for the second EC programme to combat poverty of the commission of the European Communities
Armut in Malerei und Plastik / Poverty in Painting and Sculpture, Neuer Landtag in Düsseldorf, 26.4. - 12.5.1989
boek